Anterior canal failure: ocular torsion without perceptual tilt due to preserved otolith function. Issue 9 (21st August 2003) - Strupp, M; Glasauer, S; Schneider, E; Eggert, T; Glaser, M; Jahn, K; Brandt, T
Abstract : A patient with anterior semicircular canal dehiscence syndrome underwent surgical patching that caused an isolated dysfunction of the left anterior semicircular canal postoperatively. He exhibited significant ocular torsion toward the side of the affected labyrinth (17° excyclotropia of the ipsilateral eye), but no displacement of the subjective visual vertical. This dissociation suggests that an isolated ocular torsion may occur after an anterior semicircular canal lesion. A combined ocular torsion and subjective visual vertical tilt, which is usually seen with vestibular lesions, requires an associated otolith dysfunction.